2013
DOI: 10.1371/journal.pone.0056231
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Effect of Perinatal Exposure to L-tryptophan on Circadian Clock of Primary Cell Lines Established from Male Offspring Born from Mothers Fed on Dietary Protein Restriction

Abstract: Background & AimsMaternal undernutrition programs metabolic adaptations which are ultimately detrimental to adult. L-tryptophan supplementation was given to manipulate the long-term sequelae of early-life programming by undernutrition and explore whether cultured cells retain circadian clock dysregulation.MethodsMale rat pups from mothers fed on low protein (8%, LP) or control (18%, CP) diet were given, one hour before light off, an oral bolus of L-tryptophan (125 mg/kg) between Day-12 and Day-21 of age. Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…One study demonstrated that MLP significantly altered the circadian expression of genes involved in the regulation of feeding and energy metabolism [21]. In addition, supplementation with the essential amino acid tryptophan has been shown to improve circadian function of cells isolated from MLP offspring [54]. Furthermore, offspring exposed to a different maternal dietary manipulation (maternal high fat diet) show changes in core circadian gene expression [55].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that MLP significantly altered the circadian expression of genes involved in the regulation of feeding and energy metabolism [21]. In addition, supplementation with the essential amino acid tryptophan has been shown to improve circadian function of cells isolated from MLP offspring [54]. Furthermore, offspring exposed to a different maternal dietary manipulation (maternal high fat diet) show changes in core circadian gene expression [55].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly separated into two groups (6 rats each): one group was fed a control (Ctrl) chow diet containing 18 g of protein per 100 g diet, and the second group was fed a low protein (LP) diet containing 8 g of protein plus 0.13 g of l-Trp per 100 g diet (the Ctrl diet and LP diet contained the same amount of l-Trp) (Nascimento et al 2013). Dams were maintained under controlled conditions (22 °C, 12 h/12 h dark/light cycle) with free access to their experimental diets and tap water until the evening of the 12th (embryonic day 12: E12) or until the 19th day of gestation (E19).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…14,30 These changes in both litter size and/or birth weight depend on food quality and macronutrient content, as well as the energy value of the maternal diet. [31][32][33] Recently, we reported that administering a low-protein diet through pregnancy and lactation does not alter pup birth weight, but does reduce the food intake of dams during lactation. 33 However, we did not observe any differences in food intake between lactating rats that received either the C or LE diet.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Recently, we reported that administering a low-protein diet through pregnancy and lactation does not alter pup birth weight, but does reduce the food intake of dams during lactation. 33 However, we did not observe any differences in food intake between lactating rats that received either the C or LE diet. Similar levels of intake were noted between our groups of lactating rats.…”
Section: Discussionmentioning
confidence: 99%